The effect of probiotics on gut flora, level of endotoxin and Child-Pugh score in cirrhotic patients: results of a double-blind randomized study - Lata, Jan; Novotný, Ivo; Príbramská, Veronika; Juránková, Jana; Fric, Premysl; Kroupa, Radek; Stibůrek, Oldrich (European journal of gastroenterology & hepatology, 2007)
OBJECTIVE: To determine the effect of Escherichia coli Nissle (Mutaflor, Ardeypharm GmbH, Herdecke, Germany) on the intestinal colonization, level of endotoxin and liver functions in patients with liver cirrhosis. METHODS: Thirty-nine patients with liver cirrhosis diagnosed by means of biopsy and clinical examinations were randomly allocated to treatment with E. coli Nissle or placebo for 42 days. Standard clinical examination, biochemical and hematological examinations, level of endotoxin and microbiological examination of the stool were performed before and after the treatment. RESULTS: In comparing the treatment of E. coli Nissle and placebo, significant improvement of the intestinal colonization (P<0.001) in the E. coli Nissle group was described. We found a trend of significant lowering of the endotoxemia (P=0.07) and improvement of liver functions evaluated by Child-Pugh score (P=0.06). CONCLUSION: E. coli Nissle seems to be effective in the restoration of normal colonic colonization and can probably lower endotoxemia in cirrhotic patients.
Keywords: dospělí; Double-Blind Method; Liver Cirrhosis; Escherichia coli; Humans; lidé středního věku; Middle Aged; endotoxiny; feces; Colon; jaterní cirhóza; kolon; Endotoxemia; mužské pohlaví; endotoxemie; Severity of Illness Index; stupeň závažnosti nemoci; Feces; Adult; dvojitá slepá metoda; výsledek terapie; Treatment Outcome; ženské pohlaví; Liver; Endotoxins; Probiotics; lidé; játra; Aged; senioři; Male; probiotika; Female